APLIKASI SISTEM INFORMASI PEMESANAN MAKANAN DAN MINUMAN BERBASIS MOBILE WEB (Information Technology and Telematics, 2016)
Abstract Menu ordering process at Sriya Cafe Jeparaare still manually and not computerized. The problem is how to create an information system application to order food and drinks that can be accessed via smatrphone/tablet, and also can provide sales reports to the owner.Of these problems led to the idea to create a mobile web-based applications, which in it can make an ordering menu via smartphone/tablet. The methodology used to create this application is the Waterfall method. PHP is a programming language, and the database used is MySQL. This research resulted in the mobile web-based information system applicationto order foods and drinks inSriya CafeJepara. This application can do the orderingprocess, transaction,create reports, via a local intranet network. These applications can be developed in line for the future, with improved performance and refinement preparing reports, so that applications can run better.Keywords : Mobile, Intranet, Cafe, PHP, MySQL